New Directions In The Marine Minerals Program At The U.S. Minerals Management Service - LeRon E. Bielak (International Marine Minerals Society, 1991)
The marine minerals program of the Minerals Management Service (MMSI has undergone significant changes during 1991. Formerly the Office of Strategic and International Minerals, the program has been renamed and invested with additional responsibilities. The new name, Office of International Activities and Marine Minerals, (INTERMAR) reflects its dual mission. INTERMAR'S role in the international area was broadened in January 1991 to provide the MMS with a focal point for identifying and coordinating international opportunities of mutual interest and benefit. Opportunities include energy and nonenergy minerals and a broad range of areas such as resource and environmental assessment and management, structural and operational safety, royalty management, regulatory matters and public affairs. Cooperative efforts involving information exchanges, training programs, research, and similar arrangements are receiving particular emphasis. Australia, Canada, France, Japan, Sweden, the United Kingdom and the USSR represent a growing list of countries with whom arrangements have been established. Support has also been lent to other Federal Agencies and the United Nations in areas where MMS expertise and resources can impart a significant contribution. Opportunities will also be explored which involve Pacific insular areas.